Enhancing Critical Thinking Skills Through STEM-Based Guided Inquiry on Reaction Rate - Thayban Thayban; Erga Kurniawati; Haris Munandar (Jambura Journal of Educational Chemistry, 2025)
This study aimed to analyze the effect of implementing a STEM-based guided inquiry learning model on students’ critical thinking skills regarding reaction rates. Despite the increasing emphasis on critical thinking in science education, limited research has examined how integrated STEM-based instructional models affect students’ higher-order thinking skills specifically in abstract and conceptually demanding topics like reaction rates. This study addresses that gap by evaluating the effectiveness of such a model in a real classroom setting. The research employed a quasi-experimental method with a non-equivalent control group design. A total of sixty students from SMA Negeri 1 Bolaang-Uki were selected through purposive sampling. The research instrument consisted of ten essay questions covering critical thinking indicators, validated with a Cronbach’s Alpha of 0.706, indicating high reliability. The findings showed that the implementation of the STEM-based guided inquiry model significantly improved students’ critical thinking skills. The average pretest score of 10.68% increased to 31.40% in the posttest. Hypothesis testing using an independent-sample t-test resulted in a significance value of 0.000 (< 0.05) with t₍count₎ > t₍table₎ (29.709 > 1.671). Therefore, this study confirms that the STEM-based guided inquiry model is effective in enhancing students’ critical thinking skills in learning reaction rate concepts